A rapid point-of-care ultrasound marker for muscle mass and muscle strength in older adults. (8th September 2020) - Madden, Kenneth M; Feldman, Boris; Arishenkoff, Shane; Meneilly, Graydon S
Abstract: Background/Objectives: Sarcopenia is defined as the gradual age-associated loss of both muscle quantity and strength in older adults, and is associated with increased mortality, falls, fractures and hospitalisations. Current sarcopenia criteria use dual-energy X-ray absorptiometry (DXA) measures of muscle mass, a test that cannot be performed at the bedside, unlike point-of-care ultrasound (PoCUS). We examined the association between ultrasonic measures of muscle thickness (MT, vastus medialis muscle thickness) and measures of muscle quantity and strength in older adults. Methods: A total of 150 older adults (age ≥ 65; mean age 80.0 ± 0.5 years, 66 women, 84 men) were recruited sequentially from geriatric medicine clinics. Each subject had lean body mass (LBM, by bioimpedance assay), grip strength, mid-arm biceps circumference (MABC), gait speed and MT measured. All initial models were adjusted for biological sex. Results: In our final parsimonious models, MT showed a strong significant correlation with all measures of muscle mass, including LBM (Standardised β = 0.204 ± 0.058, R 2  = 0.577, P  < 0.001) and MABC (Standardised β = 0.141 ± 0.067, R 2  = 0.417, P  = 0.038). With respect to measures of muscle quality, there was a strong significant correlation with grip strength (Standardised β = 0.118 ± 0.115, R 2  = 0.511, P  < 0.001) but not with subject performance (gait speed). Conclusions: MT showed strong correlations with both measures of muscle mass (LBM and MABC) and with muscle strength (grip strength). Although more work needs to be done, PoCUS shows potential as a screening tool for sarcopenia in older adults.